Sound Toll Registers Online. - Veluwenkamp, Jan Willem; Scheltjens, Werner; Van der Woude, Siem (TSEG - The Low Countries Journal of Social and Economic History, 2021)
In 2020, the University of Groningen and Tresoar, the Frisian Historical and Literary Center in Leeuwarden, completed the online database providing instant and free access to the complete Sound Toll Registers. This database, Sound Toll Registers Online (STRO), is already available to everyone at www.soundtoll.nl. Huygens ING is now taking over STRO from Tresoar and the University of Groningen to ensure its quality, accessibility and continuity.